Analisis Peran Penggunaan AI Chatbot Dalam Proses Pembelajaran Terhadap Pemahaman Konsep Dan Kemandirian Belajar Siswa: Analysis of the Role of Using AI Chatbot in the Learning Process on Students' Concept Understanding and Learning Independence - Ilmi Noor Rahmad; Tukiyo Tukiyo; Lia Rista; Kurnia Muhajarah; Zetty Karyati; Rahmawati Yuliyani (ITScience (Information Technology and Science), 2024)
This study investigates how AI chatbots can stimulate students' conceptual understanding and learning independence. AI chatbots as interactive tools to improve learning success have recently increased in education as AI technology develops rapidly. Chatbots powered by artificial intelligence can provide direct feedback to students, respond to their questions, and help them develop a deeper understanding of their ideas. This study used a quasi-experimental design with a quantitative methodology approach. One hundred high school students were selected as the research sample. This sample was then divided into two groups: the experimental and the control groups. The experimental group used AI chatbots as a tool in the learning process, while the control group learned without using the technology. The results showed that students in the experimental group experienced a significant increase in conceptual understanding compared to the control group. AI chatbots helped students clarify difficult-to-understand concepts, provide additional explanations, and present reflective questions that encourage critical thinking. In addition, chatbots also play a role in fostering learning independence because students become more accustomed to finding answers and solutions to their problems independently without relying entirely on teachers or peers. Furthermore, this study highlights how the use of AI chatbots not only improves academic outcomes but also contributes to building students' confidence in understanding learning materials. Thus, this study concludes that AI chatbots are an effective and innovative learning tool for improving students' conceptual understanding and learning independence.